The relationship between governance structure and risk management approaches in Japanese venture capital firms - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2004)
This paper attempts to understand what drives Japanese venture capital (JVC) fund managers to select either active managerial monitoring or portfolio diversification to manage their firms' investment risks [J. Bus. Venturing 4 (1989) 231]. Unlike U.S. venture capitalists that use active managerial monitoring to gain private information in order to maximize returns [J. Finance 50 (1995) 301], JVCs have traditionally used portfolio diversification to attenuate investment risks [Hamada, Y., 2001. Nihon no Bencha Kyapitaru no Genkyo (Current State of Japanese Venture Capital), Nihon Bencha Gakkai VC Seminar, May 7]. We found that performance pay is positively related to active monitoring and that management ownership is positively related to active monitoring and negatively related to portfolio diversification. The managerial implication of our study is that venture capitalists should be as concerned about the structure of their incentive systems for their fund managers as they are for their investee-firm entrepreneurs. Agency theory says that contingent compensation is a self-governing mechanism for individual effort that is difficult to measure and verify. When properly applied, equity ownership and performance-based pay can have powerful influencing effects on the strategic choices of managers.